Pemasangan Proteksi Kebocoran Arus Listrik pada Gedung Taman Kanak-Kanak (TK) Aisyah di Desa Muarajalai, Kecamatan Kampar Utara, Kabupaten Kampar - Adi Febrianton; Romiyadi Romiyadi; Indah Purnama Puilltri; Widya Sinta Mustika; Purnama Irwan; Yudi Dwianda (Politeknik Kampar, 2024)
Electricity is the main requirement for every activity held at the Asiyah Kindergarten school. The Aisyah Kindergarten School building, located in Muarajalai Village, has good electrical installations, but maintenance is rarely carried out. Maintenance of electrical installations is very necessary, because over time the condition of the feasibility of electrical installations really needs to be paid attention to. One effort that can be made to maintain electricity is to install extra security equipment to overcome electric current leaks. In general, homes or schools usually only use MCBs, MCBs only function for protection in the event of an overload or short circuit. However, electric current leakage cannot be protected by MCB. It is necessary to additionally install an ELCB to detect electric current leaks, so that if someone is electrocuted, the ELCB will be able to work in less than 0.1 second to cut off the electric current. Apart from protecting humans, ELCB can also protect equipment that uses electricity from electric current leaks.